(untitled) - NAFI' ATUN, ENI (LATERNE, 2013)
Play is a way to develop the knowledge, creativity (creativity), language skills, and memory. Based on this theory, selected the game "and the chain information flow", so that students have the courage to speak. Formulation of the problem: 1. How the application of techniques and word games chain information flow in German language speaking skills X.5 grade students of SMA Negeri 12 Surabaya? 2. How the learning outcomes German speaking skills through the application of techniques and word games chain information flow grade students of SMA Negeri 12 Surabaya X.5? "The purpose of research: 1. to know how the application of techniques and word games chain information flow in German language speaking skills grade students of SMA Negeri 12 Surabaya X.5. 2. to know the results of learning German language speaking skills through the application of game techniques and the chain information flow X.5 grade students of SMA Negeri 12 Surabaya. This research is a descriptive study with a qualitative approach. The results: 1. application techniques and word games chain information flow in the skills of speaking in class X.5 SMAN 12 Surabaya shows that the application of game techniques and the chain information flows effectively used in speaking skills. Students are more active and fun in the process of learning the German language, 2. From the pre-test and post-test mean of student learning outcomes in speaking skills improved from 33.9 pre-test to 65.14 at post-test. Keywords: game engineering information chain, flowing wordplay technique, speaking